Pembahasan Mengenai Front-End Web Developer dalam Ruang Lingkup Web Development - Sofyan Mufti Prasetiyo; Muhammad Ivan Prayogi Nugroho; Riris Lima Putri; Opa Fauzi (BULLET : Jurnal Multidisiplin Ilmu, 2022)
Frontend Developer is a person whose job is to present everything that interacts directly with website users. These things include all the appearance of the website (typeface, size, buttons, photos, videos, articles, etc.) as well as the data that users enter. In layman's terms, people usually refer to this position as a web developer. A Frontend Developer must be able to translate the work of a Web Designer and Backend Developer so that it can be enjoyed by website users. In terms of role, the Front End Developer's role is to develop the appearance of the site using programming languages such as CSS (Cascading Style Sheets), HTML (Hypertext Markup Language), and Javascript. Apart from that, the front end developer is also tasked with finding ways to make a responsive display or the appearance of the website. If it is opened on another platform, the appearance is not cluttered. therefore it takes sufficient skill and imagination for a front end developer to create a web appearance or interface.